Successful conjunctival socket expansion in anophthalmic patients until the age of 2 years: an outpatient procedure - El Essawy RA (Dove Medical Press, 2016)
Rania Assem El Essawy, Sameh Hassan Abdelbaky Department of Ophthalmology, Faculty of Medicine, Cairo University, Cairo, Egypt Purpose: To report the results of a simple outpatient method for soft tissue socket expansion in young children with congenital anophthalmos.Methods: Seventeen congenital anophthalmic sockets of 15 infants of a mean age of 4.2±4.4 months were fitted with specially designed serial solid acrylic shapes or hydrogel expanders using cyanoacrylate for eyelids closure when using the latter.Results: At the age of 2 years, the mean horizontal eyelid length increased from a mean of 11.6±4.5 to 19.4±4.6 mm and the volume of the last expander from a mean of 0.6±0.2 to 2.0±0.3 cm3. The specially designed acrylic shapes could be a substitute to the custom-made molds, which require general anesthesia.Conclusion: Successful increase in the horizontal eyelid length as well as the conjunctival socket volume could be achieved by a simple outpatient procedure without the need for repeated hospitalization and general anesthesia in these infants. Keywords: congenital anophthalmia, custom-made conformers, hydrogel expanders, cyanoacrylate glue